2009
DOI: 10.1111/j.1440-1746.2009.05984.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of irritable bowel syndrome in Asia: Something old, something new, something borrowed

Abstract: In this review we have unearthed epidemiological data that; support the 'old' concept of irritable bowel syndrome (IBS) as a disorder of civilization, build a 'new' symptom profile of IBS for Asia, and persuade us against the use of 'borrowed' Western diagnostic criteria and illness models by Asian societies. In the 1960s, IBS was described as a disorder of civilization. Early studies from Asia suggested a prevalence of IBS below 5%. Recent studies from Asia suggest a trend for the more affluent city states li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
160
5
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 62 publications
10
160
5
5
Order By: Relevance
“…12 However, epigastric localization of pain in Asia in general and India in particular is well-known. 13 The threshold for symptoms as per Rome III was 3 days a month as compared to 1 day per week in the Rome IV criteria. 11,12 This cut-off value is based on evidence, 14 and hence, Rome IV has been claimed to be scientifically more valid.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…12 However, epigastric localization of pain in Asia in general and India in particular is well-known. 13 The threshold for symptoms as per Rome III was 3 days a month as compared to 1 day per week in the Rome IV criteria. 11,12 This cut-off value is based on evidence, 14 and hence, Rome IV has been claimed to be scientifically more valid.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…However, in some Asian countries including India, a large proportion of patients with IBS are males. 30,31 This provided us an unique opportunity to study brain response in relation to visceral stimulation among male IBS patients. Phenotype of IBS and brain response are known to differ with respect to gender [32][33][34] and a few authors suggested that sex hormones might explain these differences.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, patients from Asia have a shorter colonic transit time than Western patients, and in South Korea most patients who experience hard stools do not meet Rome criteria for hard stools. 5,9 There are also differences within Asia; in India, patients with self-perceived constipation report a median of 2 bowel movements per day 10 and in China, where there are marked regional differences in the prevalence of constipation. 11 Similarly, and as observed in our results, there are slight differences in the prevalence of CC among Malays, Indians, and Chinese in Singapore.…”
Section: Discussionmentioning
confidence: 99%